Morphological diversity, ethnobotany, and economic value of banana plants (Musa spp.) in the Keerom lowland area, Papua Province, Indonesia (Asian Journal of Agriculture, 2025)
Abstract. Suharno, Suparno A, Yuliana, Tanjung RHR, Zebua LI, Prabawardani S. 2025. Morphological diversity, ethnobotany, and economic value of banana plants (Musa spp.) in the Keerom lowland area, Papua Province, Indonesia. Asian J Agric 9: 229-239. Bananas (Musa spp.) are an agricultural crop of significant economic value, highly sought after as a popular fruit for consumption. The global diversity of bananas is substantial and continues to grow with the emergence of new varieties, including in Papua, Indonesia. This study aims to determine the diversity of bananas based on local knowledge, ethnobotany, and the economic value of bananas in the lowland area of Keerom, Papua. Data were collected from a survey in eight villages representing the Arso, West Arso, and Skanto Districts. The diversity was determined based on morphological characters referring to descriptors for bananas, with 67 characters. Based on the local community's knowledge, 13 varieties of bananas were found. The findings also show that the population and distribution of bananas in Keerom vary. Kepok boy, kepok abu-abu, raja, barangan, and nona varieties are widely distributed, while ambon, jarum, goroho, raja nangka, susu, and merah varieties are not as widely distributed. Based on the morphological characters, supported by the results of PCA analysis and Eigenvalue tests, the banana varieties can be divided into four groups. Regarding utilization, the fruit is mostly for consumption, the leaves are for food wrappers, and the blossoms are processed as vegetables. Other parts of bananas have not been utilized optimally. The price of bananas at the consumer level averages IDR 8,500 per bunch (USD 0.5). This selling value has increased by 144.17% from the price of bananas at the farmer level. The findings also show that the banana varieties in Keerom are relatively diverse, yet most of them have not been optimally utilized. However, Indonesia has significant potential for developing food products using bananas as a primary ingredient, offering opportunities to maximize utilization and contribute to national food security.
Keywords: Bananas, food source, Keerom, Musa, traditional knowledge